Los excesos tributarios: el caso de las exportaciones - Urrunaga, Roberto (1997)
This article proposes some changes in the tax structure that have affected to Peruvian exports, in order to improve their competitiveness. This paper stresses on the analysis of two taxes: the fuel tax and the minimum income tax. One policy advice is to apply the drawback of the fuel tax paid by the firms in the production process of goods to be exported. The other policy advice is to eliminate the minimum income tax, not only to the exports firms, but also to the firms oriented to the domestic market. Because of the probability of having a great reduction in the tax co/lection in the short run as a consequence of these recommendations, the author have designed a schedule of gradual changes that cuts down the negative effects, and that should create the conditions to tax revenue to be higher in the long run.